Coaching Based Academic Supervision for Kindergarten Teacher Professionalism: Supervisi Akademik Berbasis Coaching pada Profesionalisme Guru TK - Rahyuni, Rahyuni; Marwan, Marwan; Munawar, Munawar; Idris, Jamaluddin; Mukhlisuddin, Mukhlisuddin ⁠ (Academia Open, 2026)
General Background: Quality education requires continuous teacher professional development supported by structured academic supervision. Specific Background: In practice, academic supervision in kindergartens often remains administrative and lacks reflective guidance, particularly in Aceh Tamiang Regency. Knowledge Gap: Limited studies integrate coaching techniques within academic supervision at the early childhood education level, especially in local contexts. Aims: This study examines the implementation of academic supervision through coaching techniques to improve kindergarten teacher professionalism. Results: Using a qualitative case study with interviews, observations, and document analysis, findings show supervision is conducted systematically through planning, classroom observation, reflection, and coaching-based follow-up. The approach encourages self-reflection, improvement of learning tools, adaptation of teaching strategies, and increased consistency in lesson plan implementation, classroom management, and professional responsibility. Novelty: The study provides a contextualized analysis of structured coaching integration within annual supervision cycles in kindergarten settings, highlighting its institutionalization in school quality management. Implications: Coaching-based academic supervision supports reflective and collaborative practices, strengthens teacher motivation and confidence, and contributes to improved learning quality in early childhood education. Highlights• Structured supervision stages guide reflective teaching practices• Coaching dialogue builds teacher motivation and confidence• Documented supervision cycle supports consistent classroom practices KeywordsAcademic Supervision; Coaching Techniques; Teacher Professionalism; Kindergarten Education; Reflective Practice